"I'm still terrible, don't expect much from me." Reflections on ethnographic practice in around sport (Impetus, 2021)
This work presents a journey through some methodological dilemmas of doing ethnography when we do anthropology in close sports contexts or of which we are part. From a dialogue with the field materials of my own ethnographic work, some situations that took place during the field work with "master" swimmers were analyzed, focusing the reflection on three main problems: the one that refers to the possibility of relativism and its limits, the one that emerges from the role of the researcher in field interactions and finally, the emotional issue and the place that affects play in our field work. In this way, methodological reflection will be considered as a means to improve our social knowledge.